Challenges Of Parents In Fostering Environmental Care Character Through Family-Based Waste Management Practices Among Young Children - Yunira Yunda Riswanti; Eva Manfaatin Kartadinata; Ika Rustika Zainah (FKIP UNSULTRA, 2026)
Environmental awareness in early childhood is often introduced at school, but daily habits at home do not always support the same values. This gap makes the role of parents important, especially in guiding children through simple household practices related to waste. This study aims to describe the problems faced by parents in cultivating environmental care character through family-based waste handling habits in early childhood. This research used a descriptive qualitative approach at Ma’arif Kindergarten, Kertajadi Village, Cidaun District, Cianjur Regency. Data were collected through observation, interviews, and documentation involving parents, teachers, and the school principal. The data were analyzed through data reduction, data presentation, and conclusion drawing, while validity was strengthened through source and technique triangulation. The findings show that parents have introduced children to cleanliness habits, such as throwing waste in the bin and keeping the house tidy. However, several problems remain, including limited parental understanding of waste sorting, inconsistent role modelling, limited facilities at home, low child involvement in waste handling, and weak continuity between school and family habits. This study concludes that environmental care character in early childhood requires consistent parental guidance, practical facilities, and stronger cooperation between school and family.